INSTRUMENTALISASI HUKUM PIDANA DAN PERANNYA SEBAGAI ARTILERI PENGUASA - Ahmad Mukhlish Fariduddin; Cassandra Qaliya Qazza Kartikaputri; Adela Kara Belinda (Veritas et Justitia, 2026)
Criminal law is conventionally understood as a mechanism to limit arbitrary state power and protect society from crime. However, critical legal scholarship has long emphasized its function as a political instrument capable of reinforcing existing relations of power and domination. Upon this background, this article examines the political instrumentalisation of criminal law through the cases of Tom Lembong and Hasto Kristiyanto, which serve as the principal objects of reflection in this study. This research adopts a legal philosophy approach grounded in the Critical Legal Studies (CLS) tradition, particularly drawing upon the works of Mark Tushnet and Samuel Moyn. The analysis further advances the CLS concept of oppositionalism to examine how criminal law operates within competing political interests and power structures. The study finds indications of the instrumental use of criminal law in both cases. From a CLS perspective, this phenomenon can be understood through the concept of functional underdeterminacy, whereby legal institutions and mechanisms are capable of serving identical political objectives through contrasting legal modalities. In one instance, political objectives are pursued through criminal prosecution, while in another they are advanced through the termination of criminal proceedings by means of executive clemency. These findings highlight the indeterminacy of law and its susceptibility to political contestation and strategic deployment by holders of political power.